USULAN STRATEGI AKUISISI PELANGGAN BERDASARKAN IDENTIFIKASI VARIABEL YANG MEMENGARUHI NIAT PELANGGAN UNTUK MAKAN DI TEMPAT (DINE IN) PADA WARUNK UPNORMAL CABANG SUMUR BANDUNG - Nadya Amnur, Bilqis
On January 30th, 2020, the World Health Organization (WHO) declared a global pandemic caused by the Covid 19 virus. The pandemic has caused almost all countries in the world to implement social distancing as a prevention strategy. Indonesia itself implementing Pembatasan Sosial Berskala Besar (PSBB). The PSBB has caused economic conditions in Indonesia to decline, including the Food & Beverages (F&B) sector. One of the players in this sector which also affected is the Sumur Bandung branch of Warunk Upnormal. The Sumur Bandung brach of Warunk Upnormal is currently experiencing a problem, namely the number of dine in transactions which have not yet recovered to the level before the pandemic. During the pandemic, there was a decrease of 120 130 transactions per day on weekdays and 180 190 transactions per day on weekends. After conducting research on the problem using GAP analysis and 5 Whys, it was found that the main root of the problem is the existence of moderating variables that influence customer motives to dine in. For this reason, it is necessary to identify the moderating variables in order to understand changes in customer motives for dine in. After that, an acquisition strategy is also designed based on identified motives and moderating variables, aimed to increase dine in transactions at the Sumur Bandung branch. Partial Least Square Structural Equation Modeling (PLS SEM) is used to identify and model the relationship between motives and customer intentions to dine in along with the moderating variables and their moderating effects. After identifying the motives and moderating effects that are proven to significantly influence customer intentions to dine in, an acquisition strategy is formulated. The formulation of the acquisition strategy is carried out in three stages, namely, prospecting process, selection communication channel, and development acquisition strategy. There are two target populations targeted by Warunk Upnormal, namely students and the general public (non students). In this research, the motives that significantly influenced the customer's intention to dine in in the student group were liking, socializing, visual appeal, and perceived risk of Covid 19. Meanwhile, in the general group, the pleasure and social image motives had a significant effect. There is no moderating effect that significantly affects the student group. In the general group, the government trust variable is proven to significantly have a moderating effect (weaken) the convenience motive on customer intentions to dine in. From the results of the modeling, an acquisition strategy has been designed. There are two main prospects, namely students with a majority of university students and the general public with a majority of workers. Social media, especially Instagram and TikTok, were chosen as communication channels. While the acquisition strategy is designed using content media marketing tools. After the implementation of this acquisition strategy, it is expected that the number of dine in transactions at the Sumur Bandung brach of Warunk Upnormal will increase as it was before the pandemic.